Antibacterial potential of mud lobster (thalassina anomala) extract - Nor Hasihah Md Zohir (2017, 2017)
Antibiotic resistance is one the big problems in the medicinal and pharmaceutical fields. The resistance of microorganism has been outbreak throughout the world due to their capacity to evolve and mutate. One of alternative ways to combat bacterial resistance is producing new antibacterial agent from the natural product.
Project paper (B.S.Bi.) - Universiti Putra Malaysia, 2017
English.
Keywords: Lobsters